“Excerpts from the Libro de Alexandre in El Victorial by Gutierre Díez de Games” - Casas Rigall, Juan (Troianalexandrina, 2007)
Abstract El Victorial by Gutierre Díaz de Games contains some excerpts from the Libro de Alexandre. Although the existence of these quotations has been common knowledge about since the nineteenth century, when R. S. Willis published his edition in 1934 the textual tradition of the Victorial was not totally clear, so for that reason the American academic only employed two testimonia. Using the research of R. Beltrán as a starting point, the three main copies of the Alexandrine passage in the work of Díaz de Games are now to be edited in the following.